Synthetic Versus Biological Mesh in Laparoscopic and Open Ventral Hernia Repair (LAPSIS): Results of a Multinational, Randomized, Controlled, and Double-blind Trial. Issue 1 (January 2021) - Miserez, Marc; Lefering, Rolf; Famiglietti, Federico; Mathes, Tim; Seidel, Dörthe; Sauerland, Stefan; Korolija, Dragan; Heiss, Markus; Weber, Gyorgy; Agresta, Ferdinando; Steup, Willem-Hans; Śmietański, Maciej; et al.
Abstract : Objective: The aim of this study was to investigate the approach (open or laparoscopic) and mesh type (synthetic or biological) in ventral hernias in a clean setting. Summary of Background Data: The level of evidence on the optimal surgical approach and type of mesh in ventral hernia repair is still low. Methods: Patients with a ventral abdominal hernia (diameter 4–10 cm) were included in this double-blind randomized controlled trial across 17 hospitals in 10 European countries. According to a 2 × 2-factorial design, patients were allocated to 4 arms (open retromuscular or laparoscopic intraperitoneal, with synthetic or Surgisis Gold biological mesh). Patients and outcome assessors were blinded to mesh type used. Major postoperative complication rate (hernia recurrence, mesh infection, or reoperation) within 3 years after surgery, was the primary endpoint in the intention-to-treat population. Results: Between September 1st, 2005, and August 7th, 2009, 253 patients were randomized and 13 excluded. Six of 61 patients (9.8%) in the open synthetic mesh arm, 15 of 66 patients (22.7%) in the open biological mesh arm, 7 of 64 patients (10.9%) in the laparoscopic synthetic mesh arm and 17 of 62 patients (27.4%) in the laparoscopic biological mesh arm had a major complication. The use of biological mesh resulted in significantly more complications ( P = 0.013), also after adjusting for hernia type, body mass index, and study site. The trial was prematurely stopped due to an unacceptable high recurrence rate in the biological mesh arms. Conclusions: The use of Surgisis Gold biological mesh is not recommended for noncomplex ventral hernia repair. Trial Registration: This trial was registered at controlled-trials.com (ISRCTN34532248).